Deformability-Based Microfluidic Microdroplet Screening to Obtain Agarolytic Bacterial Cells - Muta, Mikihisa; Kawakubo, Wataru; Yoon, Dong Hyun; Tanaka, Daiki; Sekiguchi, Tetsushi; Shoji, Shuichi; Ito, Mei; Hatada, Yuji; Funatsu, Takashi; Iizuka, Ryo (Analytical chemistry (Washington), 2023)
Environmental microorganisms possess enzymes that can digest macromolecules such as agarose into smaller molecules that can be utilized for growth. These enzymes could be valuable for the effective utilization of global resources. However, since most of the microorganisms on Earth remain uncultured, there is significant untapped enzymatic potential in nature. Therefore, it is necessary to develop innovative tools and strategies for exploring these enzymatic resources. To address this, we developed a method for screening microbial cells that secrete hydrogel-degrading enzymes using deformability-based microfluidic microdroplet sorting. In this method, microbial cells are encapsulated as single cells in water-in-oil (W/O) microdroplets with a hydrogel whose shape becomes deformable as the hydrogel is progressively degraded into smaller molecules. Screening is achieved using a microfluidic device that passively sorts the deformed W/O microdroplets. Using this method, we successfully sorted agarose-containing microdroplets, encapsulating single bacterial cells that hydrolyzed agarose. This method can be used to screen various hydrogel-degrading microbial cells.